(untitled) (ModaPalavra e-periódico, 2010)
This paper is to present a brief history of fashion illustration and fashion drawing, seeks to show the meanings that differentiate these two languages of drawing. Through a bibliographical review, two topics had been selected, addressing issues concerning the constitution of the fashion illustration and fashion drawing. Finally is presented the final considerations raised to help in developing the scientific field of fashion.